The Role of Reading the Al-Quran on Peace of Mind - Ahmad, Khadher bin; Huda, Dede Musa Samsul (Parahyangan Catholic University, 2023)
Al-Qur’an is the guideline for human life, the holy book that there is no doubt in it, and even the medicine for all heart ailments. But sometimes, reading al-Qur’an becomes boring and does not necessarily have promising implications. This study aims to determine the role of reading al-Qur’an on the peace of mind of male students at the modern Islamic boarding school Al-Ihsan Baleendah, Bandung. The method used in this study is a qualitative descriptive method with a case study approach. Data collection techniques using observation and interviews. The subjects of this study were five people from a population of 12 who attended the congregation of reciting Qur’an (Jamiatul Qura—JMQ) at the Al-Ihsan Baleendah Modern Islamic Boarding School, Bandung. The sampling technique used is students. After the data is collected, the researchers use a qualitative descriptive analysis technique. The results showed that the mental condition of the male students who participated in the JMQ was calm and serene. The method of reading al-Qur’an is to follow adab ahlaqiyah and inner heart. Reading al-Qur’an and following the Shari'a recommended by religion. Reading al-Qur’an significantly increases the peace of mind of male students who attend JMQ at the Al-Ihsan Baleendah Modern Islamic Boarding School, Bandung.